Integrating Porphyrinic Metal-Organic Frameworks in Nanofibrous Carrier for Photodynamic Antimicrobial Application - Huiru Zhang (MDPI AG, 2021)
The rise and spread of antimicrobial resistance is creating an ever greater challenge in wound management. Nanofibrous membranes (NFMs) incorporated with antibiotics have been widely used to remedy bacterial wound infections owing to their versatile features. However, misuse of antibiotics has resulted in drug resistance, and it remains a significant challenge to achieve both high antibacterial efficiency and without causing bacterial resistance. Here, the ‘MOF-first’ strategy was adopted, the porphyrinic metal-organic frameworks nanoparticles (PCN−224 NPs) were pre-synthesized first, and then the composite antibacterial PCN−224 NPs @ poly (ε-caprolactone) (PM) NFMs were fabricated via a facile co-electrospinning technology. This strategy allows large amounts of effective MOFs to be integrated into nanofibers to effectively eliminate bacteria without bacterial resistance and to realize a relatively fast production rate. Upon visible light (630 nm) irradiation for 30 min, the PM−25 NFMs have the best 1O2 generation performance, triggering remarkable photodynamic antibacterial effects against both S. aureus, MRSA, and E. coli bacteria with survival rates of 0.13%, 1.91%, and 2.06% respectively. Considering the photodynamic antibacterial performance of the composite nanofibrous membranes functionalized by porphyrinic MOFs, this simple approach may provide a feasible way to use MOF materials and biological materials to construct wound dressing with the versatility to serve as an antibacterial strategy in order to prevent bacterial resistance.